Dendritic glycopolymers based on dendritic polyamine scaffolds: view on their synthetic approaches, characteristics and potential for biomedical applications - Appelhans, Dietmar; Klajnert-Maculewicz, Barbara; Janaszewska, Anna; Lazniewska, Joanna; Voit, Brigitte (Chemical Society Reviews, 2015)
In this review we highlight the potential for biomedical applications of dendritic glycopolymers based on polyamine scaffolds. The complex interplay of the molecular characteristics of the dendritic architectures and their specific interactions with various (bio)molecules are elucidated with various examples. A special role of the individual sugar units attached to the dendritic scaffolds and their density is identified, which govern ionic and H-bond interactions, and biological targeting, but to a large extent are also responsible for the significantly reduced toxicity of the dendritic glycopolymers compared to their polyamine scaffolds. Thus, the application of dendritic glycopolymers in drug delivery systems for gene transfection but also as therapeutics in neurodegenerative diseases has great promise.
CRIS-Team Scopus Importer:2023-03-20